Clive Cussler's hellburner [large type] - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures, 2022)
"When Juan Cabrillo fails to capture the leader of Mexico's most dangerous drug cartel and loses an Oregon crew member in the process, he's determined to get revenge. Little does he know that the explosion he just narrowly escaped was merely the latest flash of violence from a machine of war that has existed for decades, dating from the bloodiest episode in Armenia's history. With millions of innocent civilians hanging in the balance, the Oregon's crew must unravel a tangle of international conspiracies, putting their lives on the line to find the weapon before its countdown hits zero"--